(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Mahmudkhoja Behbudiy is a modern thinker, an enlightened person who served the cause of human enlightenment. The article analyzes the writer’s ideas encouraging young people to acquire knowledge and his socio-philosophical views on the need for them to study secular sciences.